2020
DOI: 10.3390/cancers12020338
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Clinic-Based Hereditary Cancer Genetic Testing in a Population-Based Health Care System

Abstract: New streamlined models for genetic counseling and genetic testing have recently been developed in response to increasing demand for cancer genetic services. To improve access and decrease wait times, we implemented an oncology clinic-based genetic testing model for breast and ovarian cancer patients in a publicly funded population-based health care setting in British Columbia, Canada. This observational study evaluated the oncology clinic-based model as compared to a traditional one-on-one approach with a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(69 citation statements)
references
References 20 publications
5
61
3
Order By: Relevance
“…However, given the overall suboptimal testing uptake in the genetics referral based protocol and in light of emerging treatment implications of BRCA1 / BRCA2 PV, mismatch repair deficiency and potentially other defects in DNA repair, another avenue to improve genetic testing rates in patients with PDAC may be oncologist‐directed genetic testing, similar to the mainstreaming approach undertaken in breast and ovarian cancer or upfront tumor or tumor normal sequencing approaches, which may have different considerations for consent . Local experience with the oncologist‐directed genetic testing model resulted in similar patient‐reported outcomes, was acceptable to health care providers, and significantly reduced wait times for genetic testing as compared to a traditional 1‐on‐1 approach …”
Section: Discussionmentioning
confidence: 99%
“…However, given the overall suboptimal testing uptake in the genetics referral based protocol and in light of emerging treatment implications of BRCA1 / BRCA2 PV, mismatch repair deficiency and potentially other defects in DNA repair, another avenue to improve genetic testing rates in patients with PDAC may be oncologist‐directed genetic testing, similar to the mainstreaming approach undertaken in breast and ovarian cancer or upfront tumor or tumor normal sequencing approaches, which may have different considerations for consent . Local experience with the oncologist‐directed genetic testing model resulted in similar patient‐reported outcomes, was acceptable to health care providers, and significantly reduced wait times for genetic testing as compared to a traditional 1‐on‐1 approach …”
Section: Discussionmentioning
confidence: 99%
“…of included studies (44%) were from North America [34-39, 41, 44-47, 54] (Table 2). The 25 studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][51][52][53][54][55] (93%) described interventions to increase access to GC and GT through mainstreaming or UTS initiatives (S4 Table ). The study designs found were retrospective or prospective cohort studies with concurrent or historical controls (44%) [34, 36, 37, 42-47, 54, 55] or case series that reported on intervention outcomes (56%) [29-33, 35, 38-41, 48, 51-53] (Table 2).…”
Section: Plos Onementioning
confidence: 99%
“…Interventions, setting and framework. The majority of studies used complex interventions (Table 1, S4 Table ) to increase access to GC and GT, either in the routine oncology setting [29][30][31][32][33][34][35][36][37][38][39][40][51][52][53][54][55] or optimizing referral to genetic services for GC and GT [45][46][47] for ovarian or breast cancers and through optimizing access to genetic services after UTS in colorectal and endometrial cancer [39,[41][42][43][44]. The 25 studies spanned a variety of health systems (Table 2) with six studies (24%) included either a quality improvement or process model [35-37, 39, 40] or an implementation science framework [42] to guide implementation.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations